A long journey towards genome editing technologies in plants: a technical and critical review of genome editing technologies - Gallo, Dylan; Meunier, Anne-Cécile; Périn, Christophe (Frontiers in Genome Editing, 2025)
Advancements in genome editing technologies, notably CRISPR/Cas9, base editing (BE), and prime editing (PE), have revolutionized plant biotechnology, offering unprecedented precision in crop improvement to address the ongoing global warming challenge. This review provides a critical analysis of recent developments in SpCas9-based editing tools, emphasizing enhancements in editing efficiency and specificity and follow the chronological development of editing tools. We explore methodological innovations, including dual pegRNA strategies and site-specific integrases, that have expanded the potential of PE for precise gene insertions. By integrating insights into DNA repair mechanisms and leveraging SpCas9 enhancements, we outline future directions for the application of genome editing in plant breeding.